Conocimientos sobre Hipomineralización Inciso Molar y sus Alternativas Terapéuticas en Odontólogos Residentes de Postgrado de Ortodoncia de la Universidad Antonio Nariño sede Armenia 2021 (2021)
Enamel formation defects are a set of clinically visible alterations in the enamel, due to disorders that occur during mineralization or in the secretion of the enamel matrix (Naranjo Sierra, 2013) This study aimed: To evaluate and identify the knowledge about incised molar hypo mineralization (IMH) and the therapeutic alternatives used to manage the pathology, the diagnostic capacity and the time of clinical experience of general dental residents of the orthodontic specialization of the Antonio Nariño University.